Using the Woolley Motivation Typology to Heal Infidelity With Emotionally Focused Therapy - Scott R. Woolley; Réka Koren (European Journal of Mental Health)
Introduction: Infidelity is a common challenge in couple therapy and requires nuanced understandings and interventions tailored to the underlying motivations of the affair. Areas covered: This paper offers a practical framework for addressing infidelity by integrating Woolley’s (2011) motivation-based typology of affairs into the practice of Emotionally Focused Therapy (EFT) and the Attachment Injury Repair Model (AIRM). The typology categorizes infidelity into three broad categories, and seven specific types based on motivations, offering a lens through which couple therapists can focus their approach. Expert opinion: This article provides both general and specific treatment recommendations for each of the motivational types, which can help clinicians more effectively assist in ending affairs, reducing blaming, healing emotional wounds, creating safe emotional connection, and preventing future infidelity. Conclusion: This article helps fill these gaps by laying out how the Woolley (2011) motivational typology can be used to guide treatment.